Why has labour productivity slowed down in the era of financialisation? Insights from the post-Keynesians for the European Union countries - Barradas, Ricardo (2022)
This paper employs a panel data econometric approach in order to empirically ascertain the role of the phenomenon of financialisation in the deceleration of labour productivity in the European Union (EU) countries from 1980 to 2019. During that time, the EU countries suffered a huge structural transformation based on Reaganomics and Thatcherism and their financial systems have experienced strong liberalisation and deregulation, which have contributed to poor evolution of labour productivity and have revived fears around a new ‘secular stagnation’ in the era of financialisation. Grounded in post-Keynesian literature, the slowdown of labour productivity in the majority of developed economies in the last decades cannot be separated from the phenomenon of financialisation, which has occurred through four different channels, namely the weak economic performance, the decline in the labour income share, the increase in personal income inequality, and strengthening of the degree of financialisation. Our findings confirm that lagged labour productivity, economic performance, and labour income share have a positive impact on labour productivity in the EU countries, while personal income inequality and the degree of financialisation impact it negatively. Our findings also reveal that labour productivity in the EU countries in the last decades would have grown more if there had been a stronger economic performance, a smaller decline (or even a rise) of the labour income share, a smaller increase (or even a decrease) of personal income inequality, and a weakening of the degree of financialisation.